Creating Food History for Value Added Food Tourism Cham Muslim Ban Krua Community - Bunjoon, Ong (Journal of Thai Studies, 2024)
Background and objective (s) : Tourism is a large industry throughout the world. The tourism market is continuously expanding and highly competitive. The Cham Muslim Ban Krua Community is located along the Saen Saep Canal, Ratchathewi District, Bangkok, and has tourism potential. Creating a history of cultural heritage that has a unique identity is a method to promote community- based food tourism (CBT). The research for this article aimed to record the history of the food, to add value and to serve as a tool to promote food tourism through community participation. Methodology: This research is qualitative research, with storytelling as a framework. Data were collected through in-depth interviews and participatory observation, with openended questions. The interview topic consisted of two parts: personal information and information on wisdom, culture and food history. As well as, suggestions, opinions and the participation of all stakeholders was obtained. Main result: The Cham Muslim community at Ban Krua has a long history in Thai society. From the Ayutthaya period until the early Rattanakosin period, the Cham people served as volunteer troops. Currently, the Cham have the status of being a minority ethnic group, overlapping with being a Muslim minority. Globalization has connected them to an international Muslim network, bringing food culture, ingredients and cooking methods of international Muslims, including Cambodian, Vietnamese and Malay, that have been combined with their traditional food culture. At the same time, the Cham Muslim Baan Krua community has chosen to promote the identity of Cham Muslims as a minority group of Muslims through food cultural capital by integrating community history with tourism. This is a way to stimulate learning, take pride in their local history and generate income for the community. This can also preserve the ethnic identity of the Cham Muslims, as well as a universal Muslim identity and the overall image of the community as a food tourism destination – the Halal kitchen of ASEAN. Relevance to Thai Studies: The research for this article revealed how to understand the role of the history of food culture as an area to express ethnic identity as a minority group, which reflects cultural diversity in Thai society. The results can also play a role as a tool for adding value for tourism, including food tourism, ethnic tourism and cultural tourism. In addition, the results of the study are a way to further research on food tourism in ethnic communities that have unique identities. Finally, this study can provide a reflection of ethnic minority culture and regional culture in a Thai context and in Thai society with respect to other issues. Conclusion: The Cham Muslim in Ban Krua Community have chosen to use their status as a "Muslim minority", different from other Muslim communities, to raise awareness of Cham-Khmer food. However, such issues are rarely found in community activities. Therefore, the question should be asked: How can Cham-Khmer food be considered an inheritance with stories linked to traditional Cham-Khmer belief rituals used to create identity and add tourism value? The initial answer is: This can be achieved by a presentation of food history with cooking and cultural activities that separates cultural and historical issues of food tourism from religious issues.